(untitled) (Central Medical College Journal, 2026)
Background: There has been a consistent increase in the number of patients experiencing dementia, including dementia linked to Alzheimer’s disease. The effective treatment of dementia remains an unfulfilled medical requirement. In this point of view, drug treatment for this purpose has become less favorable for their prolonged time requirement and wide range of adverse effects. So, this PE may be a suitable treatment option for addressing cognitive decline as well. Objective: To assess the effects of ethanolic extract of Phyllanthus emblica (EEPE) fruit on memory performance in colchicine induced memory impaired male Long-Evans rats. Methods: This experimental study was conducted at KM Fariduddin Animal Research Laboratory, Department of Physiology, BMU on 24 male Long-Evans rats (8±2 weeks; 225±75 gm). On the basis of treatments, all rats (6 rats/group) were grouped into normal control (NC), sham control (SC), colchicine control (ColC), pre-colchicine Phyllanthus emblica treatment (Pre PE Exp). A single dose of colchicine (15 µg) was administered intrahippocampally to induce memory impairment, and subsequent behavioral changes were monitored in the Morris water maze (MWM) test in all rats. The statistical analysis was conducted using one-way ANOVA, followed by the Bonferroni post hoc test, with p≤0.05 deemed statistically significant. Results: Colchicine showed significantly (p≤0.001) higher Escape latency (EL) in training and test phase as well as in acquisition phase and significantly (p≤0.001) lower Target crossing (TC) and Time spent in target (TT) in ColC rats in comparison to those SC rats. In contrast, significantly (p≤0.001) lower EL and significantly (p≤0.001) higher TC and TT were found in Pre PE Exp rats when compared to those of ColC rats. Strikingly, no statistically significant difference was observed in any memory performance between NC and Pre PE Exp rats. Conclusion: The current study demonstrated that Phyllanthus emblica (Amloki) effectively prevented colchicine induced impairments in both working and reference memory in male long-Evans rats. Furthermore, the dosage and duration regimen of Phyllanthus emblica (Amloki) was adequate to restore these concerning effects to normal levels. Central Medical College Journal Vol 9 No 2 July 2025 Page: 84-90